With gratitude from RHiME: Reviewers 2017 - RHiME, Editor (Research and Humanities in Medical Education, 2019)
The Editorial Board of RHiME would like to thank the following experts for their outstanding contribution to the work of the journal. Without their expertise and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standards of the journal. Abha Khetarpal Amir Maroof Khan Anannya Dasgupta Anirban Chatterjee Apurba Rajbongshi Ashish Goel Navjeevan Singh Nilima Shah Olinda Timms Purnima Sharma Rajat Thawani Richa Ghay Thaman Roopa Ravindranath Sabita Shome Satendra Singh Setu Gupta John Sullivan Sudesna Ghosh Trveen Dhillon Upma Sinha